Role of Homoeopathy in Cases of Cervical Polyp (Advancements in Homeopathic Research, 2022)
Out of 23 diagnosed cases of various Cervical Lesions, 5 cases of Cervical Polyp have been treated with homoeopathic medicines on holistic basis at Gaurang Clinic and Centre for Homoeopathic Research, Lucknow. Diagnosis and periodic assessment by per vaginal examination and pelvic ultrasonography followed by holistic treatment have given encouraging results. All the cases resolved with well indicated homoeopathic medicines like Calcarea carb, Sulphur and Silicea.
Keywords: Cervical; holistic treatment; Calcarea carb; homoeopathic medicines